Diagnosis and surgical treatment of bilateral ureteral calculi, hydronephrosis, pyometra, pyocolpos, vestibulovaginal stenosis, and imperforate hymen in a dog: A rare critical case report - Kim, Sehoon; Rahman, Md Mahbubur; Chul, Park; Kim, Minju; Jeong, In Seong (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Bilateral ureteral calculi, hydronephrosis, pyometra, pyocolpos, vestibulovaginal stenosis, and imperforate hymen in a dog are uncommon and can be difficult to diagnose. The aim of this article is to report diagnostic challenges and successful surgical treatment of this rare event and the long-term outcomes. Materials and methods: A 5-year-old, spayed (partial ovariohysterectomy) female dog was primarily diagnosed with bilateral hydronephrosis and ureter obstruction due to urolithiasis along with pyometra. The urolith was removed carefully by the right-side ureterectomy, an appropriate ureteral stent was inserted from the bladder to the right kidney, and then, a vasectomy and hysterectomy were performed. The dog improved and was discharged. However, 50 days after surgery, pyocolpos due to imperforate hymen and vestibulovaginal stenosis were diagnosed and surgically corrected, and the ureteral stent was removed because the ureter had completely healed. Results: During the first admission, serum biochemistry results revealed the increased blood urea nitrogen (5.9 mg/dl), creatinine (116.2 mg/dl), amylase (1,345 U/l), and lipase (141 U/l) values. After surgical correction, all parameters returned to normal. However, 50 days after surgery, the C-reactive protein concentration (143 mg/l) and white blood cell level increased (18.4 × 109/l). After a second surgical correction, the dog recovered fully within 10 days, and no postoperative complications were observed during the follow-up of 6 months. Conclusion: This report provides diagnostic assistance and surgical treatment options for a complex urogenital case. Careful examination during puberty is recommended to prevent the associated complications of this disorder. J. Adv. Vet. Anim. Res., 7(3): 384-390, Sep 2020 http://doi.org/10.5455/javar.2020.g432